2020
DOI: 10.1111/bcp.14372
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities for the clinical implementation of therapeutic drug monitoring in oncology

Abstract: There are few fields of medicine in which the individualisation of medicines is more important than in the area of oncology. Under‐dosing can have significant ramifications due to the potential for therapeutic failure and cancer progression; by contrast, over‐dosing may lead to severe treatment‐limiting side effects, such as agranulocytosis and neutropenia. Both circumstances lead to poor patient prognosis and contribute to the high mortality rates still seen in oncology. The concept of dose individualisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 105 publications
(168 reference statements)
0
28
0
1
Order By: Relevance
“…To extend GAN-based treatment estimations from binary to various kinds of treatment variables including categorical, and continuous, [76] applied modifications to GANITE, which they named MGANITE. Estimating continuous treatment is of high importance in applications involving dosage adjustment especially in oncology [123]. One of the main modifications was a mathematical adjustment to the loss function which takes a treatment assignment vector in both the counterfactual and ITE estimation blocks, to allow for simultaneous treatment effect estimation [76].…”
Section: Treatment Effect Estimationmentioning
confidence: 99%
“…To extend GAN-based treatment estimations from binary to various kinds of treatment variables including categorical, and continuous, [76] applied modifications to GANITE, which they named MGANITE. Estimating continuous treatment is of high importance in applications involving dosage adjustment especially in oncology [123]. One of the main modifications was a mathematical adjustment to the loss function which takes a treatment assignment vector in both the counterfactual and ITE estimation blocks, to allow for simultaneous treatment effect estimation [76].…”
Section: Treatment Effect Estimationmentioning
confidence: 99%
“…Implementation of model‐informed and optimal design approaches can further contribute to overcome “classical” TDM problems, such as inappropriate timing, quality, and quantity of PK or biomarker samples. Often highlighted major concerns in traditional TDM still comprise long bioanalytical turnaround times of samples (several hours to weeks), lack of standardization in workflows, and high instrumentation costs with complex sample preparation 8 . Raising awareness for benefits of optimal (often earlier and less) sampling timepoints, streamlining internal processes to shorten turnaround times, and introducing new concepts (e.g., point‐of‐care/bedside analytics, biosensors/wearables, and home‐monitoring systems 9 ), using not only plasma, but also, for example, saliva, interstitial fluid, or capillary blood, will offer practical solutions to the challenges listed above.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…There must be better access to TDM laboratories and the provision of clinical decision support for interpreting the results of pharmacometrics that use Bayesian estimations to combine pharmacokinetics, individual patient characteristics, and drug concentrations. 23 Finally, a barrier that must be addressed to allow clinical translation of TDM is the demonstration of its economic efficacy as presented in a descriptive review by Vithanachchi et al 24 They reviewed 11 studies and noted that only a few drugs have been studied. However, all studies reviewed found TDM to be cost effective, based on established incremental cost-effectiveness ratios.…”
mentioning
confidence: 99%
“…For TDM to be translated into clinical practice, the evidence base must expand, and sampling strategies need to be simplified, perhaps by micro sampling such as using dried blood spots or using body fluids other than blood. There must be better access to TDM laboratories and the provision of clinical decision support for interpreting the results of pharmacometrics that use Bayesian estimations to combine pharmacokinetics, individual patient characteristics, and drug concentrations 23 …”
mentioning
confidence: 99%